Contamination Risk of Synovial Biopsy Cultures in Total Hip Arthroplasty: A Prospective Review of 100 Cases. Issue 6 (November 2017) - Pattyn, Christophe; De Bo, Thomas; Anthonissen, Joris; Willekens, Philippe; Claeys, Geert; Audenaert, Emmanuel A.
Introduction: Cultures of deep synovial biopsies remain an important tool in diagnosing periprosthetic joint infection, a devastating complication following total hip arthroplasty (THA). Recent reports of unexpected positive intraoperative cultures in aseptic revision arthroplasty, however, challenge the validity and interpretation of these cultures. The aim of this study was to evaluate the contamination risk of synovial biopsy cultures collected intraoperatively during primary THA of healthy subjects. Methods: Synovial biopsies for culture were collected during primary total hip arthroplasty procedures from 100 consecutive cases. The synovial biopsies were taken within the first 15 minutes after skin incision. Biopsy specimen were cultured on 4 different media for 8 or 15 days. Positive cultures were identified using Maldi-Tof spectrometry. Results: 16 cultures yielded a bacterium, suggesting a false positive result of 16%. The mean time for the cultures to become positive was 6.29 days (standard deviation [SD] 3.90) with a maximum of 15 days. Proprionibacterium acnes and Staphylococcus epidermidis were most commonly cultured with 6 positive results for both bacteria. Conclusions: Our study yielded a 16% false positive rate in cultures of synovial biopsy taken during primary total hip arthroplasty of healthy subjects, suggesting that contamination risk of these synovial biopsy cultures may be larger than assumed by clinicians.